Van regionaal naar globaal. Wat kunnen we leren van internationaal vergelijkend historisch onderzoek naar arbeid en gender? - Van Nederveen Meerkerk, Elise (TSEG - The Low Countries Journal of Social and Economic History, 2020)
This article aims to bring together three different long-term, global comparative studies on women’s work in three sectors: the textile industry, domestic service and sex work from the seventeenth century to today. Although there were notable differences between developments in these three occupations over time, it is clear that they all represent the ubiquitous precarity that runs through the history of work. Instead of viewing precarious labour as a novel development, history shows that the ILO model of ‘standard employment’ is an exception in history. Both in the Global North and in the Global South, at least half of the world’s historical population – women – often worked in underpaid, poorly organized jobs, under unequal power relations. However, despite these consistent practices of subordination, this article also highlights that within the given constrictions, female labourers who were formally powerless could exert considerable agency, using informal networks and power mechanisms that often emerged from the inherent intimacy of the labour relations they were involved in.